2012
DOI: 10.1152/ajpregu.00323.2012
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment pattern of sympathetic muscle neurons during premature ventricular contractions in heart failure patients and controls

Abstract: Premature ventricular contractions (PVC) elicit larger bursts of multiunit muscle sympathetic nerve activity (MSNA), reflecting the ability to increase postganglionic axonal recruitment. We tested the hypothesis that chronic heart failure (CHF) limits the ability to recruit postganglionic sympathetic neurons as a response to PVC due to the excessive sympathetic activation in these patients. Sympathetic neurograms of sufficient signal-to-noise ratio were obtained from six CHF patients and from six similarly age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…20 These changes on muscle sympathetic nerve activity were subsequently confirmed in heart failure patients during spontaneous PVCs, providing further support for the validity of our experimental model involving pacing-induced PVCs. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 These changes on muscle sympathetic nerve activity were subsequently confirmed in heart failure patients during spontaneous PVCs, providing further support for the validity of our experimental model involving pacing-induced PVCs. 10 …”
Section: Discussionmentioning
confidence: 99%
“…10 Of these mechanisms, the role of the autonomic nervous system (ANS) is not well understood. The ANS regulates all aspects of cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…Multiunit-MSNA was quantified as burst frequency by counting the number of bursts during a specified period of time, as burst incidence by expressing the number of burst that occurred per 100 heart beats, and as mean burst area/min (Sundlof and Wallin, 1977). Action potentials (APs) were detected and extracted from the filtered raw MSNA signal using the continuous wavelet transform (CWT) technique for AP detection as reported previously (Steinback et al, 2010; Salmanpour et al, 2010, 2011; Breskovic et al, 2011; Maslov et al, 2012). Briefly, the method uses an original mother wavelet, derived from an average human AP.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the idea that sympathoinhibition should occur if CPAP enhances cardiac index (as above), Heindl et al (2001) found a modest increase in multi-unit MSNA burst frequency in both CHF patients and healthy control subjects. Recently, our studies have explored the potential importance of quantifying actual action potential (AP) patterns in the postganglionic sympathetic nerve activity as an indicator of sympathetic patterns, rather than just the frequency of integrated bursts (Steinback et al, 2010; Salmanpour et al, 2010, 2011; Breskovic et al, 2011; Maslov et al, 2012). Specifically, multi-unit MSNA bursts are composed of several sympathetic neurons firing at the same time with burst-by-burst variations in the numbers of APs recruited (Salmanpour et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in our study of healthy subjects with Յ25 MSNA bursts/min, resting MSNA burst frequency did not influence the diameter or MAP changes following MSNA bursts. However, we speculate that substantially elevated resting MSNA burst frequency, such as observed in aging (12,19) or heart failure (17,21), may supply a neurotransmitter stimulus which overcomes the threshold for smooth muscle contraction in conduit arteries to demonstrate a decrease in compliance relative to healthy subjects, or outright vasoconstriction, depending on the degree of conduit artery smooth muscle contraction. Accordingly, it is possible that spontaneously occurring MSNA bursts may evoke vasoconstriction throughout the arterial tree in pathological overactive sympathetic states, instead of mediating an effect exclusively in resistance arteries as observed in young healthy men.…”
Section: Discussionmentioning
confidence: 93%